Pancasila sebagai Pilar dalam Sistem Hukum Anti Terorisme di Indonesia (International Forum of Researchers and Lecturers, 2024)
Pancasila, as the foundation of the Indonesian state, plays an important role in the legal system, including in the context of anti-terrorism law. This study aims to explore how the principles of Pancasila function as pillars in the formation and implementation of anti-terrorism law in Indonesia. The research method used is a qualitative approach with a literature review as the main method, which includes analysis of academic literature, legal documents, and interviews with legal experts. The results of the study indicate that the principles of Pancasila Belief in One Almighty God, Just and Civilized Humanity, Unity of Indonesia, Democracy Guided by the Wisdom of Deliberation and Representation, and Social Justice for All Indonesian People provide a moral and ideological framework underlying the creation and implementation of anti-terrorism law in Indonesia. Pancasila ensures that counter-terrorism efforts remain in accordance with the values ​​of humanity, social justice, and national unity. However, challenges such as potential human rights violations and abuse of authority need to be addressed to ensure that anti-terrorism law remains in line with the principles of Pancasila. This study recommends strengthening the enforcement of human rights, inclusiveness in policy making, and periodic evaluation and revision of anti-terrorism policies to improve their effectiveness and conformity to the country's core values.